Legal Construction of Judge Rule Number: 798 / Pid.B / 2022 / Pn.Jkt.Sel Justice Collaborator against Police Status Position Bharada Eliezer - Meirza Aulia Chairani; Trinah Asi Islami; Gustavo Marcos; Sarjiyati Sarjiyati; Angga Pramodya Pradhana (Universitas Muhammadiyah Surakarta, 2023)
Purpose: The purpose of this study is to determine the position of Bharada Eliezer against Decision Variety; 798/Pid.B/2022/PN.Jkt.Sel related to Justice Collabolator police status position and the Police Code of Ethics Decision related to Bharada Eliezer's Police Status. Methodology: This research makes use of a normative juridical research method, a conceptual technique, and a statutory technique. Results: Basically a person who commits a criminal offence of taking the life of another person is a violation of human rights and deprivation of the right to life especially when the person who commits the murder is a law enforcer and remains a member of the police, but in this case with the consideration of the judge and the consideration of the official in charge of the KKEP hearing because the perpetrator is submitted as a justice collaborator feared by irresponsible parties abused. Applications of this study: Provide input to all members of the National Police so as not to commit acts that violate the laws and regulations and the code of ethics of the police profession and tarnish the good name of the police organization or agency. Novelty/Originality of this study: There is a need to update the requirements and guidelines for justice collaborators because some criminal offenses that harm the state and extraordinary crimes really need justice collaborators to shed light on a criminal offense that was initially blurred in the facts.